PENGARUH PENDAPATAN ORANG TUA TERHADAP TINGKAT PENDIDIKAN ANAK GURU YAYASAN AL IHSAN HIDAYATULLAH BERAU: PENGARUH PENDAPATAN ORANG TUA TERHADAP TINGKAT PENDIDIKAN ANAK GURU YAYASAN AL IHSAN HIDAYATULLAH BERAU - Merlin (Prodi Ekonomi Pembangunan, Universitas Muhammadiyah Berau, 2022)
This study aims to determine and analyze the effect of parents' income on the education level of children of teachers at the Al Ihsan Hidayatullah Berau Foundation. The study was conducted on 60 people as respondents. Based on the results of the study, it can be seen that there is a significant, strong and positive effect between parental income on the education level of the teacher's child at the Al Ihsan Hidayatullah Berau Foundation, which is indicated by a correlation coefficient of 0.650 or 65%. This means that parents' income affects children's education level by 65% while the remaining 35% is influenced by other factors not included in this study. Thus, the hypothesis put forward can be accepted.